Temporal muscle thickness is an independent prognostic marker in patients with progressive glioblastoma: translational imaging analysis of the EORTC 26101 trial - Furtner-Srajer, Julia; Genbrugge, Els; Gorlia, Thierry; Bendszus, Martin; Nowosielski, Martha; Golfinopoulos, Vassilis; Weller, Michael; Van den Bent, Martin J.; Wick, Wolfgang; Preusser, Matthias (Neuro-Oncology, 2019)
AbstractBackground. Temporal muscle thickness (TMT) was described as a surrogate marker of skeletal muscle mass. This study aimed to evaluate the prognostic re